Los impactos de la globalización en el mundo laboral centroamericano - Pérez Sáinz, Juan Pablo (European Review of Latin American and Caribbean Studies, 2003)
The impact of globalization in the world of labour in Central America  This article deals with changes induced by globalization into the world of labour in Central America. The first change affects the proletarization  process with the crisis of formal employment,  mainly public employment, and the rise of new wage relations in the emerging accumulation  model. The main new labour exclusion tendency  is represented by transnational migration, the  major articulation of the region into globalization.  Finally, self-employment, in rural and urban areas, shows the persistence of a broad economy of poverty but also the emergence of new local dynamics that are leading to the fragmentation of  national labour markets. In the conclusion a number of issues, analytically  relevant beyond Central America, are considered.  First, there is a new labour heterogeneity that  challenges the analytical distinction between  formal and informal employment. Second, territoriality is being redefined and national labor markets are losing their centrality due to transnational  migration and local fragmentation. Third, contrary  to the past, exclusion tendencies predominate over  inclusive ones. And finally, employability is arising as the new way of labour integration. Resumen:Este artículo aborda los cambios inducidos por la  globalización en el mundo laboral centroamericano. El primero tiene que ver con el proceso de  proletarización que muestra la crisis del empleo  formal, especialmente del empleo público, pero también la configuración de nuevas relaciones  salariales en las actividades del modelo emergente  de acumulación. Una segunda transformación  remite a las tendencias de exclusión, donde destaca la migración transnacional, la principal modalidad de inserción de la región en la globalización. Y en tercer lugar se analiza el ámbito del  autoempleo, tanto urbano como rural, donde se  constata la persistencia de una amplia economía de la pobreza pero también se detectan nuevas  dinámicas locales que fragmentan territorialmente  a los mercados de trabajo.  Se concluye con una serie de reflexiones, que van  más allá de Centroamérica, identificando una  serie de desafíos analíticos para entender el  mundo del trabajo en la globalización. Primero,  hay una nueva heterogeneidad ocupacional que  cuestiona la pertinencia analítica de los conceptos  formal e informal. Segundo, se redefine la territorialidad y los mercados nacionales de trabajo pierden su primacía debido a las migraciones  laborales transnacionales y a las dinámicas locales  que los fragmentan. Tercero, al contrario del  pasado, las dinámicas de exclusión laboral predominan sobre las de integración. Y cuarto, la nueva dinámica de integración laboral se manifiesta en el fenómeno de la empleabilidad.